(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
The internet as a whole does not use secure links, thus information in transit may be vulnerable to interception as well. It is important to reduce the chances of the information being detected during the transmission. This is an important issue now-a- days. This paper defines the techniques used for information hiding, their applications and also discusses the drawbacks of implementing those techniques independently. The motivation for this work includes provision of protection of information during transmission without any detection of information. A PSNR calculator tool has been used for measuring the image quality factors. Further, these parameters have been used to generate graphical outputs and tabular values for comparison with the best known image steganographic techniques. The image quality metrics i.e. higher Peak Signal to Noise Ratio (PSNR) and lower Mean Square Error (MSE) obtained indicates that the proposed technique for image steganographic is good one as PSNR value is greater than 45 and MSE value lies in 0-1.